Dukungan Sosial Teman Sebaya dan Kepercayaan Diri Terhadap Penyesuaian Diri Santri Baru Kelas Vii Di Pondok Pesantren Sunan Pandanaran - Saadah, Nailis (Sekolah Tinggi Agama Islam Hasan Jufri Bawean, 2023)
New students who live in Islamic boarding schools experience various kinds of problems, one of which is adjustment. The problem of lack of adjustment is a problem that is often experienced by students in Islamic boarding schools that only study the yellow book and Islamic boarding schools that provide formal educational institutions. The purpose of this study was to find out whether peer social support and self-confidence can affect the adjustment of new students. This study uses a quantitative approach. The subjects in this study were 33 class VII-F students of SMPI SGJ. the selection of subjects in this study was based on recommendations from the school and counseling teachers. As for the scale of peer social support and self-confidence used as a data collection method, to test the hypothesis using multiple regression tests. From data management it is known that the regression coefficients obtained are: self-adjustment 34,136 + 0,332 peer social support + 0,537 self-confidence. F (2.30) = 32.328, p<0.01 with an R-squared of0.683 shows that peer social support and self-confidence have an influence of 68.3% on self-adjustment, and the remaining 31.7% is influenced by other factors. So the results of this study indicate that the self-confidence variable has a greater influence than the peer social support variable on the adjustment of new students. so it is necessary to increase the confidence of new students so that it is easier in the adjustment process